Partis politiques et médias en Grande-Bretagne : entre rivalité et complicité - Karine Rivière-De Franco (Revue LISA)
During the weeks preceding a General Election, British political parties try to convince the electorate to vote for them, but given the limited degree of direct communication, the parties need the media to transmit their messages. Their relationships are complex and behind an apparent antagonism, a real partnership sometimes develops. Indeed, political parties endeavour to influence the media in order to benefit from positive coverage, by resorting to political marketing, by hiring advisers, by giving the media the type of news that they need and by controlling press conferences and press releases. The media do not accept this manipulation and react by making independent political choices, by finding other sources of political news or by revealing the methods used by the political parties to convince voters. In other circumstances, the political parties and the media become partners, since the media enable the parties to transmit their messages without any external modification through electoral broadcasts and advertisements and sometimes they even take an active part in the parties’ electoral campaigns. Even if the political parties and the media need each other, they use and manipulate each other. During electoral campaigns, these relationships are not to be neglected because they can either facilitate or hinder the persuasion of the electorate.